Application Students' Perceptions of The Contribution of Entrepreneurship Course In Shaping Entrepreneurial Attitudes Semondo: PERSEPSI MAHASISWA TERHADAP KONTRIBUSI MATA KULIAH KEWIRAUSAHAAN DALAM MEMBENTUK SIKAP BERWIRAUSAHA - Dea Arme Tiara Harahap; Dorica Yudi Kedu; Yohanes Fantriyono Men (Institute of Educational, Research, and Community Service, 2023)
The entrepreneurship course in the higher education environment is increasingly recognized as a crucial instrument in shaping students' entrepreneurial skills and attitudes. This study aims to depict students' perceptions regarding the contributions generated by the entrepreneurship course in cultivating entrepreneurial attitudes and skills. A quantitative approach utilizing questionnaires was employed to gather data from a population of students who have taken the entrepreneurship course. Through descriptive analysis, this research reveals the outcomes of the questionnaire survey completed by the students. Findings indicate that the majority of respondents acknowledge a positive influence of the entrepreneurship course on the formation of entrepreneurial attitudes, such as self-confidence, innovative spirit, and the ability to overcome challenges. Additionally, practical skills essential for entrepreneurship, such as business planning, market analysis, and financial management, are also perceived to have improved due to this course